Performance Enhancement of Wideband Reflectarray Antennas Embedded on Paper Substrate Materials - M. Y. Ismail; H. I. Malik (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This research presents an innovative solution to address the bandwidth limitation of microstrip reflectarray antennas. Organic substrate materials with controlled compositions have been characterized to be employed as substrate materials for microstrip reflectarrays. The three proposed materials show low dielectric permittivity values of 1.81, 1.64 and 1.84 along with loss tangents of 0.053, 0.047 and 0.057 respectively. The proposed substrate materials have been verified by modelling reflectarray unit elements in CST MWS and measured using a waveguide simulator technique. The comparison between measured and simulated results show a good agreement with promising broadband performance of 312, 340 and 207 MHz for S1, S2 and S3 substrate materials respectively.